A numerical-analytic method for three-point boundary-value problems - Ronto, M. I.; Savina, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We suggest a modification of the numerical-analytic iteration method. This method is used for studying the problem of existence of solutions and for constructing approximate solutions of nonlinear ordinary differential systems with linear three-point boundary conditions of general form.